THE ROLE OF UKRAINIAN ORTHODOX CHURCH OF THE KYIV PATRIARCHATE IN CONSOLIDATION OF UKRAINE - Fihurnyi, Yurii (Київський національний університет імені Тараса Шевченка, 2019)
The article analyzes the important role of the Ukrainian Orthodox Church of the Kyiv Patriarchate (hereinafter referred to as the UOC-KP) in consolidating Ukrainian society. The Christian religion, filled with Ukrainian content and spirit, is an important part of the Ukrainian ethno-cultural space. For many centuries Ukrainian Orthodoxy has actively promoted Ukrainian ethnic, state-building, nation-building and ethnocultural processes and consolidated Ukrainians. However, since the resubordination of the Kyiv Metropolitanate in 1686 to the Moscow Patriarchate, it has become an instrument of assimilation of Ukrainianity and the destruction of Ukrainian identity. For three centuries these destructive and assimilation processes concerning Ukrainian Orthodoxy continued. Since the beginning of the disintegration of the USSR, Ukrainians began a long struggle for the elimination of totalitarian-imperial and spiritualcolonial fetters. The process of restoration of the UOC was headed by Metropolitan Filaret (Denisenko). With the active assistance of Metropolitan Filaret, on June 25, 1992, the UOC-KP was created, and on October 22, 1995, he was elected its primate. At the turn of the millennium, the UOC-KP became one of the catalysts of the consolidation processes in post-colonial Ukraine.  The UOC-KP systematically and purposefully implemented the Ukrainian language, the state outlook, the national-patriotic education among the clergy and its congregation, thereby bringing together Ukrainians and forming from the post-Soviet population conscious citizens of the Ukrainian state. The UOC-KP consistently consolidated Ukrainian society, united Ukrainian politicians with a state vision and, eventually, achieved its first victory. On October 11, 2018, the Holy Synod of the Ecumenical Patriarchate adopted a fateful decision to grant Ukrainian Orthodoxy the autocephaly.

У статті аналізується вагома роль Української Православної Церкви Київського Патріархату (далі УПЦ КП) у консолідації українства. Християнська релігія, наповнена українським змістом і духом, є важливою складовою українського етнокультурного простору. Впродовж багатьох століть Українське Православ’я активно сприяло українським етнічним, державотворчим, націєтворчим та етнокультурним процесам та консолідувало українство. Проте з часу перепідпорядкування Київської митрополії у 1686 році Московському патріархату воно стало інструментом асиміляції українства і нищення української ідентичності. Впродовж трьох століть тривали ці деструктивні й асиміляційні процеси щодо Українського Православ’я. З початку дезінтеграції СРСР українство розпочало тривалу боротьбу за ліквідацію тоталітарно-імперських й духовно-колоніальних пут. Процес відновлення УПЦ очолив митрополит Філарет (Денисенко). За активного сприяння митрополита Філарета 25 червня 1992 р була створена УПЦ КП, а 22 жовтня 1995 р. його обрано її Предстоятелем. На зламі тисячоліть УПЦ КП стала одним із каталізаторів консолідаційних процесів у постколоніальній Україні. УПЦ КП системно і цілеспрямовано впроваджувала серед кліру і своїх вірян українську мову, державницький світогляд, національно-патріотичне виховання, тим самим згуртовуючи українство і формуючи з пострадянського населення свідомих громадян Української держави. УПЦ КП послідовно консолідувала українське суспільство, об’єднувала українських політиків з державницьким світоглядом і, врешті-решт, добилася першої перемоги. 11 жовтня 2018 р. Священний Синод Вселенського Патріархату прийняв доленосне рішення про надання автокефалії Українському Православ’ю.
РОЛЬ УКРАЇНСЬКОЇ ПРАВОСЛАВНОЇ ЦЕРКВИ КИЇВСЬКОГО ПАТРІАРХАТУ У КОНСОЛІДАЦІЇ УКРАЇНСТВА
Keywords: Ukraine; Ukrainian; Ukrainian Orthodox Church of Kyiv Patriarchate; Patriarch Filaret; consolidation; Україна; українство; Українська Православна Церква Київського Патріархату; Патріарх Філарет; консолідація